Guide to business etiquette - Cook, Roy A (Prentice Hall, 2011)
Understanding the rules of etiquett -- Creating a powerful first impression -- Maintaining business relationships -- Communication etiquette -- Basic digital etiquette -- Basic business dining etiquette -- Special dining events -- Successful meetings -- Cross-cultural etiquette.